COMMUNITY STRUCTURE ECHINODERMS (ASTEROIDEA, OPHIUROIDEA, ECHINOIDEA AND HOLOTHUROIDEA) IN THE MARINE NATIONAL PARK EAST SULAWESI WAKATOBI - Eddy Yusron (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2016)
A study on Echinoderms community structure in marine national parks of Wakatobi, Southeast Sulawesi was conducted in six locations, i.e., Waha Beach, Coastal Sombo, Beach Houses, Beach Kapota, Banakawa beach, and Umala beach in October 2013. All of the six parks were located the Wakatobi territorial waters with coordinates of 5°06'25" S and 123°124'10 E. The results showed of 18 species of echinoderms representing six different types of Asteroidea, two types of Ophiuroidea, six types of Echinoidea, and four types of Holothuroidea. Group of starfish or Asteroidea was the most prominent on seagrass area. Based on the six transects sites, it turned out that the group of starfish (Asteridea) occupied a relatively high level of species richness. From the quantitative analysis values, we obtained diversity index (H) of 1.105 in Sombu, the highest evenness index (J) of 0.989 was found in Umala, and the highest species richness index values (D) of 0.132 was obtained in kapota. It seemed that all echinoderm groups were generally like seagrass microhabitat (12 types). While, sand and dead coral habitats were only occupied by 8 (eight) echinoderm groups. Keywords: echinoderms, diversity, Wakatobi, Southeast Sulawesi